Colaboração na gestão da cadeia de hortifrúti: um estudo sobre o relacionamento fornecedor-varejo supermercadista - Moura, Karina Sacilotto de (2013)
In market relations, there are several ways for agents to negotiate with each other, since open market negotiations, purely transactional, to relationships characterized by building partnerships or alliances. Therefore, an alternative is collaboration. In the context of supply chain management, collaboration among members of the same chain refers to the idea of organizations engaged in working together. On the other hand, the collaborative approach should not be adopted between the organization and all the agents with whom interacts, must choose well, for different types of collaborative relationships, according to their actual needs and to save own resources. Thus, some authors classify the types of relationships in the supply chain according to level of collaboration among the agents, and are commonly found in the literature three stages of relationship, namely: cooperation, coordination and collaboration. To identify each of these stages has a distinct set of enhancer elements and actions, these characteristics that have been raised in this study based on systematic literature review. Additionally, it was identified examples of motivating factors for companies to engage in conduct collaborative. It is worth noting that the chain studied here is of the fruits and vegetables. Described this context, the main objective of this dissertation is to characterize the different stages of the collaborative relationship between supplier of fruits and vegetables and supermarket retail chains. The method used in this study corresponds a multi case study, which examined the relationships between a supplier of fruits and vegetables and five retail supermarkets, his customers. As a result, it was identified different stages of collaborative relationship between the supplier in question and each of the retailers surveyed, for the cases studied exhibited distinct sets of characteristics in terms of elements and actions. Regarding the motivation for these companies feel encouraged to develop and maintain collaborative relationships, a set of factors was found to be the same for all relationships investigated and examples of incentives are: to ensure product availability; reduce the impact of out-of-stocks (unavailability of product) in the retail market; reduce physical losses of product; increase sales and; customer loyalty when buying fruits and vegetables in store supermarket. Therefore, through this study, it was obtained drivers capable of guiding suppliers and supermarket stores in search of collaborative management for the chain of fruits and vegetables, highlighting the opportunities associated with improving the availability of the product at shelf, thereby ensuring a better customer service.